Attitudes toward waste to energy facilities and impacts on diversion in Ontario, Canada. (April 2016) - Baxter, Jamie; Ho, Yvonne; Rollins, Yvonne; Maclaren, Virginia
Highlights: We sent a mail-back survey to three communities, two with WtE facilities and one control. We test intentions to divert waste and predictors of support for different WtE facilities. 14–18% of residents would divert less if they knew waste would go to a WtE facility. WtE incineration preferred over landfill, but only 43% in favor of hosting such a facility. Main WtE incineration facility concern is health risk; while for landfill it is odors. Abstract: Despite progress in residential waste diversion, residual waste – that fraction which cannot be recycled or composted – must continue to be managed by municipalities. Zero waste and environmental groups worry that waste-to-energy (WtE) incinerators discourage diversion, while both incineration and landfill have been stigmatized in the popular consciousness such that WtE incinerators in particular are being cancelled more often than they are approved. We conducted a mail-back survey of 217 residents in Toronto, Durham and Peel, Ontario, to understand attitudes toward diversion, levels of support for WtE incineration and WtE landfill (landfill gas recovery) facilities, and predictors of facility support. Contrary to experiences elsewhere, diversion seems threatened by WtE when measured as attitudes with 18%, and 14% agreeing that they would be less inclined to divert recyclable/compostable materials if they knew materials went to a WtE landfill or incinerator. When forced to choose between four options landfill or incineration with and without energy recovery, WtE incineration is most preferred (65%) and landfill without WtE is the least preferred option (61%). However, measurement has a large influence on public opinion results in the sense that support for WtE incineration drops to 43% when asked as a "vote in favor" question and to only 36% when measured as a 4-item index of support. When the indexes of support for landfill and WtE incineration are modeled, the prominence of odor in the landfill model distinguishes it from the WtE incinerator model which is dominated more by community and concern about health effects. Implications for policy are discussed, particularly mandatory diversion targets to accompany WtE.